A comprehensive microRNA expression profile of liver and lung metastases of colorectal cancer with their corresponding host tissue and its prognostic impact on survival - Pecqueux, Mathieu; Dienemann, Hendrik; Muley, Thomas; Büchler, Markus W. (International journal of molecular sciences, 2016)
MicroRNAs are small non-coding RNAs with a length of 18-25 nucleotides. They can regulate tumor invasion and metastasis by changing the expression and translation of their target mRNAs. Their expression is substantially altered in colorectal cancer cells as well as in the adjacent tumor-associated stroma. Both of these compartments have a mutual influence on tumor progression. In the development of metastases, cancer cells initially interact with the host tissue. Therefore, compartment-specific expression signatures of these three locations—tumor, associated stroma, and host tissue—can provide new insights into the complex tumor biology of colorectal cancer. Frozen tissue samples of colorectal liver (n = 25) and lung metastases (n = 24) were laser microdissected to separate tumor cells and the adjacent tumor-associated stroma cells. Additionally, normal lung and liver tissue was collected from the same patients. We performed a microarray analysis in four randomly selected liver metastases and four randomly selected lung metastases, analyzing a total of 939 human miRNAs. miRNAs with a significant change >2-fold between the tumor, tumor stroma, and host tissue were analyzed in all samples using RT-qPCR (11 miRNAs) and correlated with the clinical data. We found a differential expression of several miRNAs between the tumor, the tumor-associated stroma, and the host tissue compartment. When comparing liver and lung metastases, miR-194 showed a 1.5-fold; miR-125, miR-127, and miR-192 showed a 2.5-fold; miR-19 and miR-215 a 3-fold; miR-145, miR-199-3, and miR-429 a 5-fold; miR-21 a 7-fold; and, finally, miR-199-5 a 12.5-fold downregulation in liver metastases compared to lung metastases. Furthermore miR-19, miR-125, miR-127, miR-192, miR-194, miR-199-5, and miR-215 showed a significant upregulation in the normal liver tissue compared to the normal lung tissue. Univariate analysis identified an association of poor survival with the expression of miR-125 (p = 0.05), miR-127 (p = 0.001), miR-145 (p = 0.005), miR-192 (p = 0.015), miR-194 (0.003), miR-199-5 (p = 0.008), miR-215 (p < 0.001), and miR-429 (p = 0.03) in the host liver tissue of the liver metastases. Colorectal liver and lung metastases have a unique miRNA expression profile. miRNA expression in the host tissue of colorectal liver metastases seems to be able to influence tumor progression and survival. These findings can be used in the development of tailored therapies.